MAKNA PSIKOLOGIS MUSIK GONG WANING DALAM RITUAL ADAT KEMATIAN MASYARKAT HEWOKLOANG KABUPATEN SIKKA - Katharina Kojaing; Melkior Kian; Agustinus R.A. Elu (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
Gong Waning is a traditional musical instrument (gong and drum) originating from Sikka Regency, East Nusa Tenggara. This instrument functions as a dance accompaniment in various rituals, both customary (sacred) and entertainment (profane). The aim of this study was to gain knowledge about the meaning of Gong Waning's psychological music in the funeral rituals of the Hewokloang people. The theory used in this research is the theory of music psychology. In addition to the psychological theory of music, researchers also combine it with a supporting theory, namely the concept of music mythology. In his study using descriptive qualitative research using ethnographic methods where the author lives and directly experiences the ritual events of the death feast. Data collection techniques were carried out by (1) literature study, (2) observation, (3) interviews, and (4) documentation. Meanwhile, in analyzing the data, it is used in several stages, namely (1) data reduction, (2) data presentation, (3) data analysis, and (4) drawing conclusions. Furthermore, data calibration was carried out using triangulation techniques. The results showed that the presence of Gong Waning's psychological music in the death rituals of the Hewokloang community in Sikka district had a meaning of joy. Expressions of joy were expressed by the people, both the mourners and the drummers, through the strains of Gong and Waning (drum) music which presented various types of rhythmic patterns and were played by fast rhythms.